IMPLEMENTATION OF A SCHOOL INFORMATION SYSTEM AT SD AL ISTIQOMAH IN BANJAR CITY - Trisnawan Trisnawan; Kusnadia Kusnadia; Susy Rosyida (Jurnal Pilar Nusa Mandiri, 2026)
Information technology facilitates human activities in the modern era. The need for information technology has influenced various institutions, including the education sector. SD Islam Al-Istiqomah is a formal elementary education institution located in Banjar District, Banjar City, West Java. The New Student Admission System (PPDB) still uses Google Forms, which can cause delays in validating applicant data. The school fee payment process, which must be made directly, also creates difficulties for parents due to the separate locations of the administrative office and the school, often resulting in late payments. Therefore, this research aims to assist both parents and the school in carrying out their tasks more easily, securely, and efficiently. The system designed is an integrated information system for New Student Admission (PPDB) and school fee payments within a single system. The integration of these two systems simplifies centralized student data management without the need to export and import data between systems. The method used in this research is Rapid Application Development (RAD), which was selected because it can accelerate application development. The results of testing using Black Box Testing indicate that the system operates as expected without any errors.